Citric acid based (CQDs/TiO2) nanocomposites against SARS-COV-2: theoretical, photocatalytic and computational studies - Joina Gunjan Singh; Ankit Kumar Singh; Nurul Hidayah Mohamad Idris; Nattasa Kitchawengkul; Purim Jarujamrus; Hooi Ling Lee; Maria Grishina; Nadezhda Palko; Prateek Pathak; Amita Verma (Discover Nano)
Abstract In the last decade, carbon quantum dots (CQDs), a novel class of carbon-based nanomaterials, have received increasing attention due to their distinct properties. Carbon Quantum Dots/Titanium Dioxide (CQDs/TiO2) Nanocomposites were reported as potent compounds against SARS-COV-2. In this manuscript, citric acid is the carbon precursor used to synthesize carbon quantum dots (CQDs). Using a green approach, the synthesized CQD fabricates the Carbon Quantum Dots/Titanium Dioxide (CQDs/TiO2) Nanocomposites. Synthesized composites were characterized by using a UV–visible spectrophotometer, Fourier-transformed infrared (FTIR) spectrometry, X-ray diffractometry (XRD), and Scanning electron microscopy with energy dispersive X-ray analysis (SEM–EDX). Methylene blue was used to check the Photocatalytic activity of synthesized (CQDs/TiO2) nanocomposites of different concentrations. Computational modeling of agglomerates of CQD and TiO2 nanoparticles with the formula TiO2…….. Ti253O506 demonstrated two stages of the nanocomposite formation, including the formation of agglomerates with the neutral and salt-like structures with the total gain in the Gibbs free energy − 38.397 kcal/mole. In silico, Molecular docking studies of citric acid were evaluated against SARS-COV-2 protein to understand their mechanism and key amino acid interactions along with standard drug remdesivir. The photocatalytic activity of CQDs/TiO2 showed extremely promising results. Based on this study, the proposed mechanism of action of these compounds is reported. A detailed investigation of CQDs/TiO2 against SARS-CoV-2 is needed, which is another part of the research in our next manuscript.